2012
DOI: 10.1007/s00348-012-1268-6
|View full text |Cite
|
Sign up to set email alerts
|

Proper orthogonal decomposition analysis for cycle-to-cycle variations of engine flow. Effect of a control device in an inlet pipe

Abstract: This paper aims to investigate cycle-to-cycle variations of non-reacting flow inside a motored singlecylinder transparent engine in order to judge the insertion amplitude of a control device able to displace linearly inside the inlet pipe. Three positions corresponding to three insertion amplitudes are implemented to modify the main aerodynamic properties from one cycle to the next. Numerous particle image velocimetry (PIV) two-dimensional velocity fields following cycle database are posttreated to discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Recently, some researchers used the POD method to separate the in-cylinder flow into different field parts, and then studied the characteristics of each part separately. By doing so, they obtained more insightful details of the in-cylinder flow field [37][38][39].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, some researchers used the POD method to separate the in-cylinder flow into different field parts, and then studied the characteristics of each part separately. By doing so, they obtained more insightful details of the in-cylinder flow field [37][38][39].…”
Section: Introductionmentioning
confidence: 97%
“…For example, Druault et al made a POD analysis of PIV data to understand the variability change during an engine cycle [21]. Vu and Guibert focused on variations inside the engine occurring with modification of the inlet pipe [22]. Graftieaux et al [14] and Zhuang et al [23] introduced POD into vortex analysis to study the flow field characteristics in motoring optical engines.…”
Section: Introductionmentioning
confidence: 99%
“…This investigation demonstrates a first attempt to reveal the impact of intake swirl ratio (SR) on incylinder engine flow using the quadruple POD analysis technique. The concept is derived by reconstructing classical POD modes of similar features into several groups to better represent the flow field properties [22,24,29]. In a classical POD analysis, the first mode usually contains the dominant flow characteristic; then the remaining higher modes only show limited differences in kinetic energy among each other, which has led to an imprecise determination of the properties of individual mode.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, proper orthogonal decomposition (POD) was used to quantify the cycle-to-cycle flow variations within individual data sets and evaluate potential causes. POD has been used in previous studies to differentiate between cycle-to-cycle flow variations and turbulence by choosing a cut-off mode, with lower order modes being used to reconstruct the cycle-to-cycle flow variations and higher order modes used to reconstruct the turbulence 1,11 . However, Cosadia et al 12 found that determining a cut-off mode was not possible, as the cumulative energy fractions of the POD of the instantaneous velocity fields converged very slowly despite the presence of a strong in-cylinder swirl motion.…”
Section: Introductionmentioning
confidence: 99%